MEDU-05. PROGNOSTIC IMPLICATION OF TERT PROMOTER MUTATION AND TP53 NUCLEAR STAINING IN ADULT MEDULLOBLASTOMA - Li, Kay Ka-Wai (Neuro Oncol, 2019)
Medulloblastoma (MB) only uncommonly occurs in adults and there were only few clinical-molecular studies. A total of 104 adult MBs were recruited. Molecular subgroups were determined by the NanoString platform. TERT promoter (TERTp) mutation, p53 status, and MYC/MYCN amplification were evaluated by Sanger sequencing, immunohistochemistry, and FISH respectively. Patients ranged between 19–63 years old. Nearly half of the adult MBs belonged to SHH (48.1%), and WNT, Group 3, and Group 4 tumors were found in 20.2%, 15.4%, and 16.3% respectively. TERTp mutation was identified in 23/92 (25%) cases. TERTp mutation was more often detected in SHH tumors, such that 78.3% of the mutation was identified in this subgroup. TP53 nuclear staining was detected in 33/104 (31.7%) tumors and was present in all molecular subgroups. MYC (2/94; 2.1%) and MYCN (3/94; 3.2%) amplifications were rarely detected and for the former, none in Group 3. We were able to study the survivals of 70 cases with the mean and median follow-up being 42.4 and 31.0 months respectively. Molecular subgroups, including WNT, did not impact on clinical outcome. Univariate analysis revealed that TERTp mutation was associated with a shorter progression-free survival (PFS; p=0.016), but the clinical significance was only maintained in the WNT tumors when subgrouped. Furthermore, patients with TP53 nuclear staining showed significantly shorter PFS (p=0.013) and overall survival (OS; p<0.001). When patients were stratified according to molecular subgroups, TP53 remained as strong predictor for PFS in Group 3 (p=0.004) and Group4 (p=0.018) tumors and OS in SHH (p=0.012) and Group 3 (p=0.046). Our study seems to suggest that SHH is not as over-represented in adult MB as previously reported, molecular subgroups may not be as strong prognostic indicators in adult MB as in pediatric patients and that TERTp mutation and TP53 are poor prognosticators across all subgroups.